A New Method of Seismic Source Parameter Estimation of a Locked-Segment Cracking Event. (6th June 2022) - Yang, Bai-Cun; Bai, Jian-Xin; Duan, Yong-Ting; Cheng Cheng,
Abstract : Locked segments are widely present in the slip surface of large rock slopes and seismogenic faults of rock underground engineering. Each cracking occasion of the locked segment results in a seismic event. Accurate determination of the seismic source parameters of a locked-segment cracking event is crucial for the reliable evaluation of rock-mass stability associated with slopes and underground openings. The theoretical framework for calculating seismic source parameters in previous studies is mostly based on the stick-slip model, which is not applicable to describing the locked segment's damage process, and research on seismic source parameter estimation of a locked-segment cracking event is insufficient. Hence, based on the principle of energy conversion and distribution during the locked segment's damage process, we proposed an equation for the radiated seismic energy of a locked-segment cracking event. Using this equation, we established a mechanical relationship between the earthquake magnitude and the stress drop or shear strain increment (or maximum coseismic displacement) of a locked-segment cracking event. Typical case studies of rock slope and rock underground engineering showed that the proposed calculation method of seismic source parameters was reliable. In addition, this paper discusses the controversy surrounding the relationship between earthquake magnitude and stress drop. Relevant results lay a firm physical foundation to accurately calculate the seismic source parameters of a locked-segment cracking event and obtain detailed insights into the generation mechanism of the locked-segment cracking event.